A case of naevus sebaceus of Jadassohn of the scalp in Jamaica. Issue 12 (28th December 2021) - Williams, Geoffrey; Diaz, Gabriella; Blake, Garfield
Abstract: Naevus sebaceus (NS), also referred to as NS of Jadassohn, is a rare non-melanocytic congenital cutaneous hamartoma with mainly sebaceous differentiation. NS has pluripotent potential with the possible evolution of benign and/or malignant neoplastic transformation. Literature of clinical audit and retrospective analyses conclude that there is no need for prophylactic excision except for cases in which malignant transformation is suspected. Although malignant transformation is rare, there are psychosocial issues with which to contend. We present a case of a 5 year-old girl with a cerebriform mass to her right parietal scalp, which was present at birth.